Development of a conceptual model of childhood asthma to inform asthma prevention policies - Mohsen Sadatsafavi; Stuart E Turvey; Padmaja Subbarao; Malcolm R Sears; Theo J Moraes; Amin Adibi; Piush J Mandhane; Tae Yoon Lee; Allen B Becker (BMJ Open Respiratory Research)
Background There is no definitive cure for asthma, as prevention remains a major goal. Decision analytic models are routinely used to evaluate the value-for-money proposition of interventions. Following best practice standards in decision-analytic modelling, the objective of this study was to solicit expert opinion to develop a concept map for a policy model for primary prevention of asthma.Methods We reviewed currently available decision analytic models for asthma prevention. A steering committee of economic modellers, allergists and respirologists was then convened to draft a conceptual model of paediatric asthma. A modified Delphi method was followed to define the context of the problem at hand (evaluation of asthma prevention strategies) and develop the concept map of the model.Results Consensus was achieved after three rounds of discussions, followed by concealed voting. In the final conceptual model, asthma diagnosis was based on three domains of lung function, atopy and their symptoms. The panel recommended several markers for each domain. These domains were in turn affected by several risk factors. The panel clustered all risk factors under three groups of ‘patient characteristic’, ‘family history’ and ‘environmental factors’. To be capable of modelling the interplay among risk factors, the panel recommended the use of microsimulation, with an open-population approach that would enable modelling phased implementation and gradual and incomplete uptake of the intervention.Conclusions Economic evaluation of childhood interventions for preventing asthma will require modelling of several codependent risk factors and multiple domains that affect the diagnosis. The conceptual model can inform the development and validation of a policy model for childhood asthma prevention.